2019
DOI: 10.1080/1828051x.2019.1604088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of colony performances of honeybee (Apis Mellifera L.) housed in hives made of different materials

Abstract: Numerous flowering plants rely on bees for pollination. Any natural or anthropogenic factor that threatens colony survival can have a large impact on plant production. This study investigates the effects of manmade hives built from different materials and how these may influence colony growth. Ten each of three hive types were selected, wooden, polystyrene and composite insulated hives. Factors of adult bee numbers, brood development, nectar flow period weight gain, bee flight activity, aggression response, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This could be attributed to the fact that African honeybees prefer woody habitats in nature. This is in line with the work by Erdoğan [8] who earlier reported that colonies housed in wooden hives achieved superior performance over polystyrene hives. Contrastingly, previous work by Alburaki and Corona [11] showed that hives made of polyurethane provided better insulation than hives made of softwood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could be attributed to the fact that African honeybees prefer woody habitats in nature. This is in line with the work by Erdoğan [8] who earlier reported that colonies housed in wooden hives achieved superior performance over polystyrene hives. Contrastingly, previous work by Alburaki and Corona [11] showed that hives made of polyurethane provided better insulation than hives made of softwood.…”
Section: Discussionsupporting
confidence: 92%
“…The effectiveness of honeybee growth and output is also greatly influenced by the temperature and humidity of the surrounding environment, necessitating some modifications to the beehives [7]; (Abou-Shaara, 2014). It is advised that materials that can isolate heat and humidity be used to make modern apiculture hives more suited for honeybee colonies [8]. Insulation for hive covers is essential in the winter when temperatures may fall below zero [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, decreases the overall hive strength and productivity (Li et al, 2019). Former reports have demonstrated increased thermoregulation efficiency in modified hives designed for both hot and cold climates (Abou-Shaara et al, 2013;Erdoğan, 2019;Floris et al, 2020;Alburaki and Corona, 2021), increasing yield and decreasing mortality rates. Although conventional Langstroth hives have prevailed since 1852, exploring the use of different materials according to the local climate may offer advantages to keeping the hive microclimate within an appropriate physiologic range (Mitchell, 2015).…”
Section: Contextmentioning
confidence: 99%
“…7 It must be considered that several studies suggest that Langstroth hives, traditionally used around the world, lack insulating capacity, which directly affect microclimate and makes thermoregulation more difficult. [8][9][10] Thermo regulation of honeybee (apismellifera l.) Hives under extreme temperatures Volume 6 Issue 3 -2022…”
mentioning
confidence: 99%